Pengaruh Financial Technology dan Manajemen Keuangan Terhadap Perilaku Konsumtif Mahasiswa - Kuswanto, Kuswanto; Aryanti, Sepha; Arief, Hidayatul (Universitas Negeri Surabaya, 2024)
This research aims to determine the influence of financial technology and financial management on student consumption behaviour. The population in this study was 168 students from the Economic Education Study Program at Jambi University Class of 2019-2020 and 118 people were sampled using proportionate stratified random sampling. This research is quantitative research with an ex post facto method. Data collection techniques use Google Forms. Data were analyzed using multiple regression statistical techniques. Based on the analysis, it shows that the financial technology variabel has a positive and significant effect on consumer behaviour. The more students use financial technology in financial transactions, the more consumptive their behaviour will be. Financial management variabels have a positive and significant effect on consumer behaviour. The better students manage their finances, the more consumptive their behaviour becomes. Simultaneously, financial technology and financial management have a positive and significant effect on student consumption behaviour. The higher level of use of financial technology accompanied by good financial management results in increasingly consumerist behaviour among students. The resulting regression model statistically has a very high ability to predict the influence of the use of financial technology and financial management on student consumptive behavior because it is supported by an R-square value of 96.8%. Based on the results of these findings, it is based on students' preferences in meeting their daily needs by making financial plans that suit their needs and consistently allocating them through wise use of financial technology so as not to behave consumptively.